Carboxy derivatised Ir(iii) complexes: synthesis, electrochemistry, photophysical properties and photocatalytic hydrogen generation1. Issue 22 (14th June 2015) - Paul, Avishek; Das, Nivedita; Halpin, Yvonne; Vos, Johannes G.; Pryce, Mary T.
<x xml:space="preserve">Abstract</x> In this contribution the synthesis and characterisation of a series of novel mixed ligand iridium(iii) complexes, functionalised with a carboxy ester or phosphonate groups are reported.